24-6k=6(k-4)

Simple and best practice solution for 24-6k=6(k-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 24-6k=6(k-4) equation:


Simplifying
24 + -6k = 6(k + -4)

Reorder the terms:
24 + -6k = 6(-4 + k)
24 + -6k = (-4 * 6 + k * 6)
24 + -6k = (-24 + 6k)

Solving
24 + -6k = -24 + 6k

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '-6k' to each side of the equation.
24 + -6k + -6k = -24 + 6k + -6k

Combine like terms: -6k + -6k = -12k
24 + -12k = -24 + 6k + -6k

Combine like terms: 6k + -6k = 0
24 + -12k = -24 + 0
24 + -12k = -24

Add '-24' to each side of the equation.
24 + -24 + -12k = -24 + -24

Combine like terms: 24 + -24 = 0
0 + -12k = -24 + -24
-12k = -24 + -24

Combine like terms: -24 + -24 = -48
-12k = -48

Divide each side by '-12'.
k = 4

Simplifying
k = 4

See similar equations:

| 0.4y+0.65x=60 | | 24-6k=6k(4-k) | | 6(1+4a)=-114 | | 3(9y+3)-9=2y+21 | | 39+0.75x=x | | (4z+2)+(5z-3)= | | T*4-3=12 | | 5x^2+10x+46=0 | | 14=-0.5x^2+46 | | 3(4x-1)=9x+6 | | 18x-6=20x-12 | | A*5+6=10 | | -30de+12=18d | | 5t+6-2r=7r-10 | | y+9x^3y=0 | | 4x+1=4x-2 | | 3x-5x+3=x-7+10 | | -5(x+2)+3x=-5(x-3)+3x | | 70x^3+112x-1=0 | | 108=-6(x-8)-4x | | 7n=50+24 | | Y-3=-(x-5) | | (5x+y)+(2x+6y)= | | 2(x+9)=26 | | 3*8x=1.5e^2x | | x^4+0.5x^3-6x^2+5=0 | | g-(-7)=13 | | 33=6a+2 | | 20p-(7+2p)= | | z^2+(4+2i)z+(2-3i)=0 | | 39-15y=-31-5y | | 21y^14-7y^4=0 |

Equations solver categories